Literature Review: Hubungan Agregat Komunitas dengan Strategi Pencegahan Risiko dalam Kesehatan Kerja - M Bachtiar Safrudin; Aisyah Nur Sabila; Siti Khadijah; Fauziyah Ardelia; Nanda Imut Tyyah; Nurhayati Sipahutar (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Occupational safety and health (OSH) is a fundamental component in protecting workers from risks that may threaten their safety, health, and productivity. Across various community aggregates both in formal sectors such as industry and healthcare facilities, and informal sectors such as workshops, home industries, and tourism communities the level of hazards and risks varies widely, requiring specific prevention strategies. This literature review aims to analyze the relationship between community aggregate characteristics and the effectiveness of risk prevention strategies within the context of occupational health. The study employs a systematic literature review of articles published between 2023 and 2025 that discuss occupational risk exposure, safety management, and promotive and preventive interventions. The findings indicate that each community group has different needs in identifying and controlling risks. In the informal sector, OSH education, personal protective equipment (PPE) use, and community-based interventions have been shown to increase hazard awareness and reduce workplace accidents. In the formal sector, analytical methods such as HIRARC, FMEA, and HAZOP help identify risks in a structured manner and determine control priorities, particularly for ergonomic, mechanical, biological, and chemical hazards. The review also highlights that the success of OSH interventions is strongly influenced by active worker participation, adherence to standard operating procedures (SOPs), continuous supervision, and management support. Overall, a comprehensive understanding of community aggregate characteristics is essential for designing more targeted, collaborative, and sustainable risk prevention strategies to improve occupational health and safety.